(untitled) (Revista de História Regional, 2007)
The text has its origin analyzing the notion of crisis in the capitalist society, indicating how the crisis is expressed within the States regulation, then it is possible to discuss the proposal of the Reform of the State Apparatus presented by Fernando Henrique Cardosos government. The search for a historical interpretation of the Brazilian society since the 1970s is the condition to consider the current impasse about the debates on the reform of the State Apparatus